2016
DOI: 10.1016/j.actbio.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A meso-scale layer-specific structural constitutive model of the mitral heart valve leaflets

Abstract: Fundamental to developing a deeper understanding of pathophysiological remodeling in mitral valve (MV) disease is the development of an accurate tissue-level constitutive model. In the present work, we developed a novel meso-scale (i.e. at the level of the fiber, 10–100 μm in length scale) structural constitutive model (MSSCM) for MV leaflet tissues. Due to its four-layer structure, we focused on the contributions from the distinct collagen and elastin fiber networks within each tissue layer. Requisite collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
103
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 68 publications
5
103
0
Order By: Relevance
“…straightening) of fibres in an ensemble, and is thus referred to as the 'recruitment function'. It has been found that, in normal MV leaflets, D is largely independent of angle [16]. Following anisotropic permanent set and/or growth during pregnancy, however, this assumption is no longer valid if the recruitment function parameters are defined with respect to the natural stress-free reference configuration (b s ) of the tissue.…”
Section: Constitutive Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…straightening) of fibres in an ensemble, and is thus referred to as the 'recruitment function'. It has been found that, in normal MV leaflets, D is largely independent of angle [16]. Following anisotropic permanent set and/or growth during pregnancy, however, this assumption is no longer valid if the recruitment function parameters are defined with respect to the natural stress-free reference configuration (b s ) of the tissue.…”
Section: Constitutive Modelmentioning
confidence: 99%
“…In brief, the total stress in the leaflet in this solid mixture model was assumed to be the weighted linear sum of the stresses borne by the underlying collagen fibre network, elastin fibre network and the remainder of the tissue matrix, with each stress being scaled by the mass fraction of its corresponding phase. The matrix phase has been shown to have very low tensile stiffness and thus to contribute very little to the mechanical behaviour of the total tissue [16]. Therefore, in this study, we neglected the matrix phase and instead attributed all the stress in the tissue to the collagen and elastin fibre networks.…”
Section: Constitutive Modelmentioning
confidence: 99%
See 3 more Smart Citations